On the taxonomic status of apostolepis roncadori lema, 2016 and apostolepis vittata (Cope, 1887) (serpentes: Dipsdidae) Sobre el estatus taxonómico de apostolepis roncadori lema, 2016 y apostolepis vittata (Cope, 1887) (serpentes: dipsadidae) - Entiauspe-Neto, Omar Machado; Tiutenko, Arthur (Revista Latinoamericana de Herpetologia, 2020)
Apostolepis Cope, 1862 is a speciose dipsadid snake genus. Among its more than 30 taxa, several species are known only from small series of specimens. The lack of basic information about morphological variations and natural history has resulted in a difficult taxonomic history of the group. We revisit the taxonomic status of the recently described Apostolepis roncadori Lema, 2016 and argue about its synonymy with a previously long-known species Apostolepis vittata Cope, 1887, considering their diagnostic characters either do not differ or the difference can be attributed to intraspecific variation.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Elapomorphini; Neotropical; Synonym; Systematics